Generation Z and Coffee Tourism Trends: Preferences, Experiences, and Potential in Yogyakarta - Bulqis Purnama Dewi; Hermawan, Hary; Afif, Fuadi (Lembaga Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Pariwisata Ampat Yogyakarta, 2024)
This study aims to identify the preferences of Generation Z in choosing thematic coffee tourism in the Special Region of Yogyakarta, based on the concepts of Something to See, Something to Do, and Something to Buy. Using a mixed-method approach, this research involved 100 Generation Z respondents selected through purposive sampling. The collected data reveals that Generation Z favours coffee tourism experiences that are both educational and interactive, with coffee plantation landscapes, coffee harvesting and processing, and direct interactions with farmers and baristas as the main attractions. The findings also indicate that coffee tourism is not yet widely popular but has great potential if well-promoted. Respondents show a preference for coffee tourism packages priced between IDR 50,000 and IDR 100,000, with a tour duration of 1-3 hours. In conclusion, coffee-themed tourism designed with Generation Z preferences in mind can effectively introduce local coffee and support the development of Indonesia's tourism economy.